The First Record of Two Species of Dactylogyrus (Monogenetic Trematodes) in Iraq From Diyala River Fishes, Diyala Province - -Ameer, K. N. Abdul (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Two species of monogenetic trematodes of the genus Dactylogyrus were recorded in the present paper for the first time in Iraq from two freshwater fishes from Diyala river, Diyala province. The first species, D. bocageii Alvarez Pellitero, Vicente et Gonzalez Lanza, 1981 was recorded from gills of Aspius vorax, the second species, D. lenkorani Mikailov, 1967 was recorded from gills of Barbus sharpeyi. The descriptions and measurements of these parasites as well as their illustrations were given.